Challenge for cause: Bias screening procedures and their application in a Canadian courtroom - Schuller, Regina A.; Erentzen, Caroline; Vo, Alice; Li, David (Psychology, Public Policy, and Law, 2015)
Although there is a presumption of juror impartiality in Canadian law, this presumption may be set aside where there is evidence of widespread racial bias in the community from which the jury will be drawn. Following R. v. Parks (1993), defendants are entitled to challenge potential jurors if they believe that racial bias will interfere with the ability of the jurors to judge the case impartially. Although the challenge procedure has been in place for some time, little attention has been given to whether this procedure effectively screens jurors for bias. The present study provides an in-depth examination of the challenge for cause procedure through a detailed analysis of the jury selection phase of a sample of cases that occurred in an Ontario courthouse between 2009 and 2011. A total of 32 defendants and 1,392 prospective jurors were involved in these proceedings. Only a small minority of potential jurors (8.3%) reported that they would be unable to judge the case impartially due to the defendant’s race. Despite this, triers found on average 20.9% of prospective jurors unacceptable, suggesting that something other than expressed bias motivated the determination of juror acceptability. (PsycInfo Database Record (c) 2025 APA, all rights reserved)